THE MEDIATING EFFECT OF SOCIAL SUPPORT ON THE RELATIONSHIP BETWEEN JOB DEMAND AND WORK STRESS AMONG EMPLOYEES IN A SHARED SERVICES COMPANY - R. A. SIAM, MOHAMMED (International Journal of Psychosocial Rehabilitation, 2020)
The conception of stress was announced to physiology in 1936 by Hans Selye, who defined it as a non-specific response of the organism to any pressure or demand (Tonhajzerova & Mestanik, 2017). Stress has in general been viewed as a set of neurological and physiological feedbacks that serves an adaptive function (Ashare, Lerman, Cao, Falcone, Bernardo, Ruparel, and Loughead, 2016). Traditionally, stress research has been oriented toward studies involving the body's reaction to stress and the cognitive processes that influence the perception of stress (Wahbeh, 2014).Though social perspectives of the stress response have noted that different people experiencing similar life conditions are not necessarily affected in the same manner (Bowling, 2014), Lindholm (2013) defined stress as “a particular relationship between a person and the environment that is appraised by the person as taxing or beyond his or her resource and endangering his or her well-being." In the advanced study, the concept was then comprised by psychology and other social sciences, as well as by social policy-makers, and ultimately made its way to everyday vocabulary (Milczarek, Schneider & González, 2009). Research into the societal and cultural influences of stress raises the necessity to reexamine how stress is defined and studied. By applying this notion to a working situation, the European Agency for Safety and Health at Work has defined work-related stress as experienced when the demands of the work environment exceed the workers’ ability to cope with (or control) them (Milczarek, Schneider, & González, 2009). Stress is a vigorous condition in which an individual is confronted with an opportunity, constraint, or demand related to what he or she desires and for which the outcome is perceived to be both uncertain and important (Beheshtifar, Hoseinifar, and Moghadam, 2011).It is important to understand that stress could affect the performance and mental and physical health of the individual at work. The reasons behind and manifestations of work stress must be identified.Therefore, this research would carry with objectives as follows:1. To study the contribution of job demand on work stress of employees from a shared services and outsourcing (SSO) company.2. To study the influence of social support on work stress of employees from SSO company.3. To determine if social support mediates the relationship between job demand and work stress of employees from SSO Company.